2018
DOI: 10.1038/s41422-018-0016-8
|View full text |Cite
|
Sign up to set email alerts
|

An NF90/NF110-mediated feedback amplification loop regulates dicer expression and controls ovarian carcinoma progression

Abstract: Reduced expression of DICER, a key enzyme in the miRNA pathway, is frequently associated with aggressive, invasive disease and poor survival in various malignancies. Regulation of DICER expression is, however, poorly understood. Here, we show that NF90/NF110 facilitates DICER expression by controlling the processing of a miRNA, miR-3173, that is embedded in DICER pre-mRNA. Since miR-3173 in turn targets NF90, a feedback amplification loop controlling DICER expression is established. In a nude mouse model, NF90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 57 publications
(78 reference statements)
6
45
0
Order By: Relevance
“…Following loss of NF90, differential expression analysis (fold change ≥ 1.5 or ≤ 0.667; AdjP-value ≤ 0.05) showed that 212 precursor miRNAs, corresponding to 268 mature miRNAs, were upregulated while 126, corresponding to 149 mature miRNAs, were downregulated ( Figure 1B). MiRNAs that have previously been shown to be modulated by NF90, miR-7-1 (14) and miR3173 (19), were found to be upregulated in HepG2 cells following loss of NF90 ( Figure 1B, red dots).…”
Section: Nf90 Modulates the Abundance Of A Subset Of Human Mirnasmentioning
confidence: 84%
See 4 more Smart Citations
“…Following loss of NF90, differential expression analysis (fold change ≥ 1.5 or ≤ 0.667; AdjP-value ≤ 0.05) showed that 212 precursor miRNAs, corresponding to 268 mature miRNAs, were upregulated while 126, corresponding to 149 mature miRNAs, were downregulated ( Figure 1B). MiRNAs that have previously been shown to be modulated by NF90, miR-7-1 (14) and miR3173 (19), were found to be upregulated in HepG2 cells following loss of NF90 ( Figure 1B, red dots).…”
Section: Nf90 Modulates the Abundance Of A Subset Of Human Mirnasmentioning
confidence: 84%
“…Total RNA was extracted from HepG2 cells using TRIzol reagent (Thermo Fisher Scientific) and RNA was treated with DNAse I (Promega) according to the manufacturer's instructions. RNA was used for RT-PCR and modified 5' RLM-RACE as described previously (19). Supplementary Table S3.…”
Section: Rt-qpcr Modified 5' Rlm Race and Rna Emsamentioning
confidence: 99%
See 3 more Smart Citations